(b) Calculate the sum of each of the following geometric series: \( \begin{array}{ll}\text { (1) } 6+12+24+\ldots+6144 & \text { (2) } 4-8+16 \ldots+16384 \\ \text { (3) }-5+15-45+\ldots-3645 & \text { (4) } 100-10+1-\ldots+\frac{1}{10000} \\ \text { (5) } 200\left(1+(1,01)+(1,01)^{2}+\ldots+(1,01)^{28}\right) & \text { (6) }-12-6-3-\ldots-\frac{3}{256} \\ \text { (7) } x y^{2}+x y+x+\ldots+\frac{x}{y^{12}} & \text { (8) } x^{5}-x^{3}+x-\ldots+\frac{1}{x^{11}}\end{array} \)
Real Tutor Solution
Answer
Solution
Sign in to Unlock Answers for Free!
A Learning Platform Trusted by Millions of Real Students and Teachers.
Reviewed and approved by the UpStudy tutoring team
Mind Expander
To find the sum of each of these geometric series, we can apply the formula for the sum of a finite geometric series, which is \( S_n = a \frac{1 - r^n}{1 - r} \), where \( a \) is the first term, \( r \) is the common ratio, and \( n \) is the number of terms. (1) For the series \( 6 + 12 + 24 + \ldots + 6144 \): - Here, \( a = 6 \), \( r = 2 \), and \( n = 13 \) (since \( 6144 = 6 \cdot 2^{12} \)). - The sum is \( S_{13} = 6 \frac{1 - 2^{13}}{1 - 2} = 6 \cdot (8192 - 1) = 6 \cdot 8191 = 49146 \). (2) For \( 4 - 8 + 16 + \ldots + 16384 \): - In this case, \( a = 4 \), \( r = -2 \), and \( n = 14 \) (since \( 16384 = 4 \cdot (-2)^{13} \)). - The sum is \( S_{14} = 4 \frac{1 - (-2)^{14}}{1 - (-2)} = 4 \cdot \frac{1 - 16384}{3} = 4 \cdot \frac{-16383}{3} = -21844 \). (3) For \( -5 + 15 - 45 + \ldots - 3645 \): - Here, \( a = -5 \), \( r = -3 \), and \( n = 8 \) (since \( -3645 = -5 \cdot (-3)^{7} \)). - The sum is \( S_{8} = -5 \frac{1 - (-3)^{8}}{1 - (-3)} = -5 \cdot \frac{1 - 6561}{4} = -5 \cdot \frac{-6560}{4} = 8200 \). (4) For \( 100 - 10 + 1 - \ldots + \frac{1}{10000} \): - In this series, \( a = 100 \), \( r = -0.1 \), and \( n = 5 \) (since \( \frac{1}{10000} = 100 \cdot (-0.1)^{5} \)). - The sum is \( S_{5} = 100 \frac{1 - (-0.1)^{5}}{1 - (-0.1)} = 100 \cdot \frac{1 - (-0.00001)}{1.1} = 100 \cdot \frac{1.00001}{1.1} = 90.9091 \). (5) For \( 200\left(1 + (1.01) + (1.01)^{2} + \ldots + (1.01)^{28}\right) \): - Here, \( a = 1 \), \( r = 1.01 \), and \( n = 29 \). - The sum inside the parentheses is \( S_{29} = 1 \frac{1 - (1.01)^{29}}{1 - 1.01} \approx 1 \cdot \frac{1 - 1.34885}{-0.01} = 34.885 \), so \( 200 \cdot 34.885 \approx 6977 \). (6) For \( -12 - 6 - 3 - \ldots - \frac{3}{256} \): - Here, \( a = -12 \), \( r = \frac{1}{2} \), and \( n = 9 \) (since \( -\frac{3}{256} = -12 \cdot \left(\frac{1}{2}\right)^{8} \)). - The sum is \( S_{9} = -12 \frac{1 - \left(\frac{1}{2}\right)^{9}}{1 - \frac{1}{2}} = -12 \cdot \frac{1 - \frac{1}{512}}{\frac{1}{2}} = -12 \cdot 2 \cdot \frac{511}{512} = -12 \cdot \frac{1022}{512} = -24.149 \). (7) For \( xy^{2} + xy + x +